2020
DOI: 10.1051/e3sconf/202018301003
|View full text |Cite
|
Sign up to set email alerts
|

Conservation Amid COVID-19 Pandemic: Ecotourism Collapse Threatens Communities and Wildlife in Morocco

Abstract: COVID-19 pandemic has had huge impacts on multiple industries and sectors, not just ecotourism and wildlife protection in Morocco. Ecological health and wildlife are a critical resource for the country’s tourism sector recovery. Conservation is considered as one of the industries that are hit hard by the COVID-19 pandemic. Many of the threats facing biodiversity and protected areas have been exacerbated during and following, the outbreak with practices such as poaching, wildlife trafficking, and forest logging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 33 publications
0
22
0
Order By: Relevance
“…Several studies have suggested that such livelihood loss coupled with increased human confinement and limited conservation enforcement would have inadvertently increased likelihood of poaching of wildlife ( Bakar and Rosbi, 2020 ; Bates et al, 2020 ; Buckley, 2020 ; Rutz et al, 2020 ). Such spikes in poaching during lockdown have already been witnessed in southern African parks ( Roth, 2020 ), Morocco ( Cherkaoui et al, 2020 ), and Italy ( Manenti et al, 2020 ). Similar trends have also been observed in Asia, including India ( Dalton, 2020 ; Special Correspondent, 2020 ; Ghosal and Casey, 2020 ; Saeed et al, 2020 ).…”
Section: Introductionmentioning
confidence: 84%
“…Several studies have suggested that such livelihood loss coupled with increased human confinement and limited conservation enforcement would have inadvertently increased likelihood of poaching of wildlife ( Bakar and Rosbi, 2020 ; Bates et al, 2020 ; Buckley, 2020 ; Rutz et al, 2020 ). Such spikes in poaching during lockdown have already been witnessed in southern African parks ( Roth, 2020 ), Morocco ( Cherkaoui et al, 2020 ), and Italy ( Manenti et al, 2020 ). Similar trends have also been observed in Asia, including India ( Dalton, 2020 ; Special Correspondent, 2020 ; Ghosal and Casey, 2020 ; Saeed et al, 2020 ).…”
Section: Introductionmentioning
confidence: 84%
“…Some protected areas also reported fewer disturbances of animals due to lower visitation rates, and fewer incidences of road kill (Smith et al, 2021). However, enhanced illegal trafficking of wildlife was reported in some regions as livelihoods collapsed or enforcement efforts were reduced (Cherkaoui et al, 2020; CS1, Table 1).…”
Section: Incomes and Livelihoodsmentioning
confidence: 99%
“…Pinder et al, 2020;Yang et al, 2020). The persecution (illegal or otherwise) of wildlife perceived as pests, including endangered species such as wolves and raptors, has also reportedly increased, although quantifiable data are lacking (Cherkaoui et al, 2020). Species susceptible to COVID-19 transmission, such as great apes, are at greater risk of contracting the disease from visitors unless strict safeguarding measures are implemented, with unknown but possibly severe consequences for population persistence (CS2, CS6, Table 1).…”
Section: Covid-19mentioning
confidence: 99%
See 2 more Smart Citations